Kinetic modeling and optimization of operating parameters for transvinylation of lauric acid - Kamble, Sanjay P.; Manjarekar, Onkar; Mawale, Ravi; Kulkarni, Bhaskar D.; Chowdary, Naresh; Gupte, Milind Y.; Barve, Prashant P. (International Journal of Chemical Kinetics, 2012)
The transition metal complex catalyzed transvinylation of carboxylic acid with vinyl acetate monomer is of significant interest to industry. The palladium complex catalyzed transvinylation of lauric acid using vinyl acetate monomer is a reversible reaction. In present article, design of experiments (DOE) statistics is used to study effects of various operating parameters on transvinylation of lauric acid. The kinetic parameters forward and backward rate constants and the thermodynamic parameters such as equilibrium constant and energy of activation of the transvinylation of lauric acid were estimated using the Dynochem model. The optimum operating parameters for the transvinylation of lauric acid were then predicted using the Dynochem model and verified by performing the actual experiments to validate the model. It was found that the experimental results match with the predicted one. (c) 2012 Wiley Periodicals, Inc. Int J Chem Kinet 44: 624634, 2012